Insight into resistance to ‘Candidatus Liberibacter asiaticus,’ associated with Huanglongbing, in Oceanian citrus genotypes - Alves, Mônica N.; Raiol-Junior, Laudecir L.; Girardi, Eduardo A.; Miranda, Maéva; Wulff, Nelson A.; Carvalho, Everton V.; Lopes, Sílvio A.; Ferro, Jesus A.; Ollitrault, Patrick; Peña, Leandro (Frontiers in Plant Science, 2022)
Huanglongbing (HLB), the most destructive citrus disease, is associated to unculturable, phloem-limited Candidatus Liberibacter species, mainly Ca. L. asiaticus (Las). Las is transmitted naturally by the insect Diaphorina citri. In a previous study, we determined that the Oceanian citrus relatives Eremocitrus glauca, Microcitrus warburgiana, M. papuana and M. australis and three hybrids among them and Citrus were full-resistant to Las. After two years of evaluations, leaves of those seven genotypes remained Las-free even with their susceptible rootstock being infected. However, Las was detected in their stem bark above the scion-rootstock graft union. Aiming to gain understanding on the full-resistance phenotype, new experiments were carried out with the challenge-inoculated Oceanian citrus genotypes through which we evaluated: 1) Las acquisition by D. citri fed onto them; 2) Las infection in sweet orange plants grafted with bark or budwood from them; 3) Las infection in sweet orange plants top-grafted onto them; 4) Las infection in new shoots from rooted plants of them; and 5) Las infection in new shoots of them after drastic back-pruning. Overall, results showed that insects that fed on plants from the Oceanian citrus genotypes, their canopies, new flushes and leaves from rooted cuttings evaluated remained qPCR-negative. Moreover, their budwood pieces were unable to infect sweet orange through grafting. Furthermore, sweet orange control leaves resulted infected as insects fed onto them and graft-receptor susceptible plants. Genomic and morphological analysis of the Oceanian genotypes corroborated that E. glauca and M. warburgiana are pure species while our M. australis accession is a M. australis × M. inodora hybrid and M. papuana probably a M. papuana × M. warburgiana hybrid. E. glauca × C. sinensis hybrid was found coming from a cross between E. glauca and mandarin or tangor. Eremocitrus × Microcitrus hybrid is a complex admixture of M. australasica, M. australis and E. glauca while the last hybrid is a M. australasica × M. australis admixture. Confirmation of consistent full-resistance in these genotypes with proper validation of their genomic parentages is essential to map properly genomic regions for breeding programs aimed to generate new Citrus-like cultivars yielding immunity to HLB.